Clinical pharmacogenetics of angiotensin II receptor blockers in Iraq - Hany A Al-Hussaniy; Alaa F Hassan; Amjad I Oraibi; Atheer M R. Al-Juhaishi; Fatima A Naji; Zahraa S Al-Tameemi (Wolters Kluwer Medknow Publications, 2023)
Background: Clinical pharmacogenetics is a rapidly growing field that focuses on the study of genetic variations and their impact on drug metabolism, efficacy, and safety. Angiotensin II receptor blockers (ARBs) are commonly used to treat hypertension in Iraq but not all patients respond equally to these drugs. Aim: This article aims to review the current evidence on the clinical pharmacogenetics of ARBs in Iraq and its implications for personalized medicine. Materials and Methods: We conducted a literature review of studies on the genetic variations that affect the response to ARBs in Iraq. We also reviewed the prevalence of these genetic variants in the Iraqi population and discussed the potential clinical implications for personalized medicine. Results: The most studied genetic variations associated with ARB response in Iraq are the angiotensin-converting enzyme gene insertion/deletion polymorphism and the angiotensin II type 1 receptor gene A1166C polymorphism. The angiotensin-converting enzyme gene insertion/deletion polymorphism is associated with variability in response to ARBs, while the angiotensin II type 1 receptor A1166C polymorphism is associated with an increased risk of cardiovascular events in patients treated with ARBs. The prevalence of these genetic variants in the Iraqi population varies widely depending on the region and ethnic group. Conclusion: The clinical pharmacogenetics of ARBs in Iraq suggests that pharmacogenetic testing could improve the selection and dosing of ARBs in Iraqi patients, leading to better patient outcomes and cost-effective healthcare.